Theatre Under Duress: The Transformative Power of Performance in Times of Crisis - Greene, Jonah E. (Tufts Archival Research Center, 2020)
A Senior Honors Thesis for the Department of Theatre, Dance, and Performance Studies exploring the phenomenon of theatrical performance produced in times of great duress. Two case studies shape this exploration: performances created in ghettos and concentration camps during the Holocaust, and performances by incarcerated inmates in modern-day prison systems, focusing on prisons in the United States and United Kingdom. Advisor: Professor Barbara Wallace Grossman.